The Prevalence of Anemia among the Adolescent Girls in a Selected College in Kanchipuram (Medico Legal Update, 2020)
In developing nations, the adolescent group is progressively exposed to health issues and young girls areincreasingly weak due to anemia. An observational study was conducted to assess the prevalence of anemiaamong the adolescent girls in a selected college in Kanchipuram. The objectives were to assess the sociodemographicvariables of the adolescent girls, to assess the prevalence of anemia among the adolescent girlsand to associate the prevalence of anemia and the socio-demographic variables of the adolescent girls. Thecross sectional design was used to conduct the study. The setting of the study was a selected Allied HealthScience college in Chennai. Adolescents in the age group of 17 to 19 years were selected as samples forthe study. The convenience sample technique was used to select the samples. The sample size was 32. Theresults showed that 16 (50.0%) of the participants belong to the age 17 years and 18 years equally and themajority of the study participants 27 (84.0%) belong to nuclear family and 05 (16.0%) of the populationbelong to joint family and the 08 (25.0%) of the study participants were vegetarian and 24 (75.0%) of themwere non vegetarian. The level of hemoglobin showed that majority of the study participants 22 (56.0%)suffer low hemoglobin level.